THE ROLE OF WORK COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. ASTRA INTERNATIONAL TBK-TSO - Novita Mardiani (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
Study this aim to know the influence of competence work and discipline work on the performance of employee PT. ASTRA INTERNATIONAL TBK-TSO (Auto 2000) Jombang area . This study uses a quantitative approach. The population in the survey is the employee marketing section _ as many as 30 employees. Sample study using saturated sampling ( census ). Data used is the primary data obtained through a questionnaire. Analysis Tool is analysis multiple linear regression using SPSS. The results show that competent and disciplined work can increase the performance of employees at PT. Astra International Tbk -TSO Jombang region .